The Role Of Biological Components Of Water Ecosystems At Formation Sediments - Мірошніченко, О. П.; Васенко, О. Г. (Man and Environment. Issues of Neoecology, 2014)
The questions about the role of the aquatic ecosystems biological component in the formation of sediment were reviewed. The role of aquatic organisms (phytoplankton, higher aquatic plants, invertebrates, and other groups of organisms) in self-purification of aquatic ecosystems and the formation of sediments were analyzed.